Level of Practice of Social Studies Teachers in 21st Century Work and Life Skills A Field Study in the Primary Stage (First Cycle) in Latakia City - عباس, رشا; روعة عارف جناد , (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of this research is to identify the level of practice of social studies teachers in the primary stage (first cycle) in the city of Latakia in the 21st century skills related to work and life (flexibility and adaptation, social interaction, leadership and responsibility, communication, cooperation), and to study whether there are statistically significant differences between the means of their scores according to the variables (gender, number of years of experience, educational qualification). The research adopted the descriptive approach, and the research community included all first-grade primary school teachers in the city of Latakia, who numbered (2225) teachers distributed over (23) schools according to the official statistics of the Directorate of Education in Latakia City. A simple random sample was drawn at a rate of (15%) from the original community, so that the number of its members reached (334) teachers, where the researcher distributed the questionnaire, the research tool, to them, and (318) complete and valid questionnaires were retrieved for statistical analysis. The results showed that the level of practice of 21st-century skills among the research sample was high, and there were no statistically significant differences between the means of the scores of social studies teachers in the primary stage (first cycle) in Latakia city in the level of their practice of 21st-century work and life skills according to the variables of gender, years of experience, and academic qualifications.